Basic hypergeometric polynomials with zeros on the unit circle - Area, I.; Godoy, E.; Lamblem, R. L.; Ranga, A. Sri [UNESP] (Elsevier B.V., 2013)
The objective in this manuscript is to present two specific sequences of polynomials with elements given in terms of basic hypergeometric polynomials or q-hypergeometric polynomials. It is shown that the zeros of these polynomials are simple and that they lie exactly on the unit circle. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Basic hypergeometric polynomials; Zeros; Orthogonal polynomials on the unit circle; Self-inversive polynomials